Reliability of the double-folding potential for fusion cross sections of light systems - Abdul Aziz, Azni; Yusof, Norhasliza; Firihu, Muhammad Zamrun; Abu Kassim, Hasan (American Physical Society, 2015)
We study the fusion reaction of light systems with one-dimensional barrier penetration model using the α-α double-folding cluster (DFC) potential. We especially analyze the fusion cross sections of the 12C + 12C, 16O, 24Mg, 28Si, 16O + 16O, 24Mg + 24Mg, 28Si, and 28Si + 28Si reactions. The results are compared with the one obtained with M3Y double folding (DFM) and the Aky¨uz-Winther (A-W) potentials. It is found that the calculations with DFM and DFC potentials can reproduce the experimental data much better than the calculations using the A-W potential. We also carried out an analysis on the astrophysical aspect of the 12C + 12C, 16O, and 16O + 16O reactions. The calculations using DFC and DFM potentials could fit the S-factor data reasonably well. However, the calculated reaction rates are lower than the compilation of Caughlan and Fowler at low temperatures. In the important range of temperatures in stellar evolution, the DFC potential reproduces very satisfactory fitting to the experimental cross section and the S-factor data and gives a consistent prediction of astrophysical reaction rates. This finding indicates that the DFC potential could be used as an alternative potential to study the fusion reactions in the astrophysical interest.